Synthesis, Characterization, and Antimicrobial Activity of Methyl-2-aminopyridine-4-carboxylate Derivatives - S. Nagashree; P. Mallu; L. Mallesha; S. Bindya (Journal of Chemistry)
A series of methyl-2-aminopyridine-4-carboxylate derivatives, 3a–f, were synthesized in order to determine their in vitro antimicrobial activity. The chemical structures of the synthesized compounds were confirmed by elemental analyses, FT-IR, and 1H NMR spectral studies. Among the synthesized compounds, 3c and 3d showed good antimicrobial activity compared to other compounds in the series.